The effect of negative emotions on smoking craving: the chain-mediating role of self-control and self-exempting beliefs - Zhao, Yixin; Li, Yong; Shu, Yang; Wang, Xiaoyan; Wang, Wen; Yang, Lian (Frontiers in Psychiatry, 2025)
BackgroundPrevious studies have demonstrated that negative emotions increase smoking cravings. To date, the specific action pathways between negative emotions and smoking cravings remain unclear. This study aimed to investigate the association between negative emotions and smoking cravings, as well as to determine whether self-control and self-exempting beliefs serve as mediating variables for this association.MethodsA cross-sectional study was conducted in Sichuan Province, Southwest China, from January 2022 to April 2023. Negative emotions, self-control, self-exempting beliefs, and smoking cravings were assessed using questionnaires. Descriptive statistics and one-way analysis of variance were used to analyze smoking cravings and their influencing factors. Correlation and mediation effect analyses were conducted to investigate the intrinsic correlations among the research variables.ResultsThis study involved 1293 current smokers. We observed significant differences in smoking cravings across demographic groups. In addition, negative emotions, self-control, and self-exempting beliefs were all significantly associated with smoking cravings (p< 0.05). After controlling for socio-demographic variables, both self-control and self-exempting beliefs exhibited a chain mediating role between negative emotions and smoking cravings. Negative emotions exerted a direct effect on smoking cravings, with an effect value of 0.0694, accounting for 61.29% of the total effect value. Self-control and self-exempting beliefs mediated the relationship between negative emotions and smoking cravings, with effect values of 0.0334 and 0.0081, representing 29.47% and 7.16% of the total effect value, respectively. The chain mediating effect value of self-control and self-exempting beliefs was 0.0024, representing 2.08% of the total effect value.ConclusionThis study demonstrates that self-control and self-exempting beliefs partially mediate the relationship between smokers’ negative emotional states and their cravings to smoke. It is important to pay timely attention to the emotional changes of smokers, enhance their ability to maintain self-control in negative emotional states, and mitigate smoking-related self-exempting beliefs to help smokers better cope with smoking cravings caused by emotional changes, prevent relapse, and achieve long-term smoking cessation goals.